International trade in natural resources: Practice and policy - Michele Ruta; Anthony J. Venables (Center for Economic Studies and ifo Institute (CESifo), 2012)
Natural resources account for 20% of world trade, and dominate the exports of many countries. Policy is used to manipulate both international and domestic prices of resources, yet this policy is largely outside the disciplines of the WTO. The instruments used include export taxes, price controls, production quotas, and domestic producer and consumer taxes (equivalent to trade taxes if no domestic production is possible). We review the literature, and argue that the policy equilibrium is inefficient. This inefficiency is exacerbated by market failure in long run contracts for exploration and development of natural resources. Properly coordinated policy reforms offer an avenue to resource exporting and importing countries to overcome these inefficiencies and obtain mutual gains.
Keywords: F10; F13; Q30; 330; natural resources; trade; export tax; tariff escalation; OPEC; WTO; terms of trade